1993
DOI: 10.1021/np50094a004
|View full text |Cite
|
Sign up to set email alerts
|

Bisamides from Aglaia Species: Structure Analysis and Potential to Reverse Drug Resistance with Cultured Cells

Abstract: The structure of pyramidatine [1], a new bisamide alkaloid from leaves of Aglaia pyramidata, was determined through extensive nmr studies, including homonuclear COSY, NOESY, APT, HETCOR, and selective INEPT techniques. Revision of the 13C-nmr assignment of piriferine [2], an alkaloid previously isolated from A. pirifera, was achieved by examination of several 2D nmr spectra (homonuclear COSY, NOESY, and HETCOR) and confirmed by selective INEPT nmr experiments. Evaluation of the cytotoxic potential of the two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 10 publications
4
28
1
Order By: Relevance
“…The number of extracts capable of exerting this biological response was very small. However, four different alkaloid systems, the Aglaia bisamide alkaloid, piriferine (Saifah et al, 1993), some iboga indole alkaloids from Peschiera laeta (Mart. ex A.…”
Section: The Potential Of Alkaloids In Lead Discoverymentioning
confidence: 99%
“…The number of extracts capable of exerting this biological response was very small. However, four different alkaloid systems, the Aglaia bisamide alkaloid, piriferine (Saifah et al, 1993), some iboga indole alkaloids from Peschiera laeta (Mart. ex A.…”
Section: The Potential Of Alkaloids In Lead Discoverymentioning
confidence: 99%
“…C-NMR spectroscopic data indicated that this compound is an analog of cinnamic acid-derived bisamide, reported in the Aglaia species. 5 The location and position of three units, 1,4-butanediamine, cinnamoyl, and 2-(4-hydroxyphenyl)acetic acid moiety, were completely assigned by the observed HMBC correlations (Fig. 2).…”
Section: Notesmentioning
confidence: 88%
“…The compound 3 was identified as pyramidatine by comparison of its data to the published values. 5 All isolates obtained from active fractions were evaluated for their inhibitory activity against NO production in LPS-induced RAW 264.7 cells, and compounds 1 and 2 displayed moderate inhibition of NO production with IC50 values of 65.3 and 83.4 µg/mL, respectively, while compound 3 was found to be inactive.…”
Section: Notesmentioning
confidence: 99%
“…Previous phytochemical studies on the genus Aglaia have revealed the presence of a variety of compounds with interesting biological activities, including rocaglamides, aglains, bisamides, triterpenoids, lignans, and steroids [2]. In continuation of our investigation on the chemistry of the Aglaia plants [3,4], we undertook a chemical constituent study on the 95% ethanolic extract of the leaves of Aglaia perviridis Hiern, which led to the isolation of a new cinnamic acid-derived bisamide 1 and a new sesquiterpenoid diglycoside 2, together with 11 known compounds, including three 3,4-secodammarane triterpenoids: aglinin A [5], shoric acid, and eichlerianic acid [6]; two C 27 nortriterpenoids: eichlerialactone [7] and cabraleahydroxylactone [8]; two pregnane-type steroids: 2b,3b-dihydroxy-5a-pregn-17(Z)-en-16-one and 2b,3b-dihydroxy5a-pregn-17(E)-en-16-one [9]; two alkaloids: pyramidatine [10] and piperine [11]; one lignan: (þ )-eudesmin [12]; and one sterol: 7a-hydroxysitosterol [13]. Eichlerialactone was first reported from this genus, and the other compounds were obtained from this plant for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report the isolation and structural elucidation of 1 and 2. 3.41 (2H, br q, J ¼ 6.1 Hz), 3.36 (2H, br q, J ¼ 6.1 Hz), and 1.64 (4H, qui-like, J ¼ 6.0 Hz), indicating a cinnamic acid-derived bisamide [10].…”
Section: Introductionmentioning
confidence: 99%